2021
DOI: 10.1200/jco.21.01761
|View full text |Cite
|
Sign up to set email alerts
|

Germline Genetic Testing for Women With Breast Cancer: Shifting the Paradigm From Whom to Test to Whom NOT to Test

Abstract: Approximately 3% of patients with breast cancer have a pathogenic or likely pathogenic variant (mutation) in a high-risk breast cancer gene, such as BRCA1 and BRCA2 (BRCA1/2) and PALB2, which increases breast cancer risk more than fourfold. 1,2 Another roughly 3% have a germline mutation in a moderatepenetrance breast cancer gene, such as ATM or CHEK2, which confers a two-to threefold increased risk of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“… 27 In response, some clinicians have suggested that universal testing would entail challenges and potential harms; therefore, guidelines should be revised to include women with breast cancer at age of diagnosis of 60 years or younger or 65 years or younger, but still exclude older patients with no family history. 7 , 8 Yet in the studies cited pointing to potentially inappropriate mastectomies or unnecessary oophorectomies performed for moderate-risk variants, the majority of patients described were aged 50 years or younger. In the present study, PGV prevalence was distributed similarly across all age groups, and for most patients older than 65 years, clinicians reported a change in clinical recommendation made and positive impact on patient health outcome as a result of testing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 27 In response, some clinicians have suggested that universal testing would entail challenges and potential harms; therefore, guidelines should be revised to include women with breast cancer at age of diagnosis of 60 years or younger or 65 years or younger, but still exclude older patients with no family history. 7 , 8 Yet in the studies cited pointing to potentially inappropriate mastectomies or unnecessary oophorectomies performed for moderate-risk variants, the majority of patients described were aged 50 years or younger. In the present study, PGV prevalence was distributed similarly across all age groups, and for most patients older than 65 years, clinicians reported a change in clinical recommendation made and positive impact on patient health outcome as a result of testing.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, the American Society of Breast Surgeons released a consensus guideline to recommend that genetic testing be offered to all patients with a personal history of breast cancer . In response, some clinicians have suggested that universal testing would entail challenges and potential harms; therefore, guidelines should be revised to include women with breast cancer at age of diagnosis of 60 years or younger or 65 years or younger, but still exclude older patients with no family history . Yet in the studies cited pointing to potentially inappropriate mastectomies or unnecessary oophorectomies performed for moderate-risk variants, the majority of patients described were aged 50 years or younger.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has impact in terms of treatment decision-making, as it was reported that up to 30% of patients who had universal genetic testing had modifications to their treatment based on their carrier status [ 10 ]. This proportion may increase further with the recent approval of Poly (adenosine diphosphate–ribose) polymerase (PARP) inhibitors as a treatment option for breast cancer patients who are germline BRCA carriers [ 12 , 13 ]. In terms of cost, universal BRCA genetic testing was reported to be cost effective in upper and upper-middle income countries [ 14 ], and if the cost of testing is lowered further to a threshold of USD172 per test, it can be cost-effective in low-middle income countries as well [ 14 ].…”
Section: Introductionmentioning
confidence: 99%